Musings on Music A letter from conductor - Carewe, John 1933- (Dance Books Ltd., Alton,Hampshire (UK), 2004)
The apparent tension between dancers and choreographers on the one side and musicians on the other neatly laid bare.
Dance to the Music of Times, the article by Brendan McCarthy in Dance Now (Vol. 12, No 4).